Comparison of nuclear grade and immunohistochemical features in situ and invasive components of ductal carcinoma of breast Comparação do grau nuclear e perfil imunoistoquímico nos componentes in situ e invasivo de carcinoma mamário - Fernando Nalesso Aguiar; Henrique Nogueira Mendes; Carlos E. Bacchi; Filomena Marino Carvalho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2013)
PURPOSE:To compare the prognostic and predictive features between in situ and invasive components of ductal breast carcinomas. METHODS:We selected 146 consecutive breast samples with ductal carcinoma in situ (DCIS) associated with adjacent invasive breast carcinoma (IBC). We evaluated nuclear grade and immunohistochemical expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), cytokeratin 5/6 (CK5/6), and epidermal growth factor receptor (EGFR) in both components, in situ and invasive, and the Ki-67 percentage of cells in the invasive part. The DCIS and IBC were classified in molecular surrogate types determined by the immunohistochemical profile as luminal (RE/PR-positive/ HER2-negative), triple-positive (RE/RP/HER2-positive), HER2-enriched (ER/PR-negative/HER2-positive), and triple-negative (RE/RP/HER2-negative). Discrimination between luminal A and luminal B was not performed due to statistical purposes. Correlations between the categories in the two groups were made using the Spearman correlation method. RESULTS:There was a significant correlation between nuclear grade (p<0.0001), expression of RE/RP (p<0.0001), overexpression of HER2 (p<0.0001), expression of EGFR (p<0.0001), and molecular profile (p<0.0001) between components in situ and IBC. CK 5/6 showed different distribution in DCIS and IBC, presenting a significant association with the triple-negative phenotype in IBC, but a negative association among DCIS. CONCLUSIONS: Our results suggest that classical prognostic and predictive features of IBC are already determined in the preinvasive stage of the disease. However the role of CK5/6 in invasive carcinoma may be different from the precursor lesions. OBJETIVO: Comparar características prognósticas e preditivas entre os componentes in situ e invasivo de carcinomas ductais da mama. MÉTODOS: Selecionamos 146 amostras mamárias consecutivas com carcinoma ductal in situ (CDIS) associado com carcinoma invasivo (CI) adjacente. Avaliamos grau nuclear e a expressão imunoistoquímica de receptor de estrogênio (RE), receptor de progesterona (RP), receptor do fator de crescimento epidérmico humano 2 (HER2), citoqueratina 5/6 (CK5/6) e o receptor do fator de crescimento epidérmico (EGFR) em ambos componentes, in situ e invasor, e a porcentagem de células marcadas pelo Ki-67 no componente invasivo. CDIS e CI foram classificados nos tipos moleculares, determinados pelo perfil imunoistoquímico, como luminal (RE/RP-positivo/HER2-negativo), triplo-positivo (RE/RP/HER2-positivo), HER2-puro (RE/RP-negativo/HER2-positivo) e triplo-negativo (RE/RP/HER2-negativo). A discriminação entre luminal A e Luminal B não foi feita por motivos estatísticos. Correlações entre as categorias dos dois grupos foram feitas pelo método de correlação de Spearman. RESULTADOS: Houve significante associação entre grau nuclear (p<0,0001), expressão de RE/RP) (p<0,0001), superexpressão de HER2 (p<0,0001), expressão de EGFR (p<0,0001) e perfil molecular (p<0,0001) entre os componentes in situ e invasivo. CK5/6 mostrou distribuição distinta em CDIS e CI, apresentando significante associação com o fenótipo triplo-negativo em CI, mas uma associação negativa ente os CDIS. CONCLUSÕES:Nossos resultados sugerem que as características prognósticas e preditivas clássicas dos CI estão já determinadas no estágio pré-invasivo da doença. Entretanto, o papel da CK5/6 no carcinoma invasivo pode ser diferente daquele das lesões precursoras.